Literary tourism: exploring Charles Dickens’ Rochester - Hasan, Md. Mahmudul (2019)
Among all the places that inspired Dickens’ work, Rochester High Street is perhaps the most remarkable for the intensity of its association with the novelist. Fortunately, modernisation has not been able to encroach upon High Street to eliminate the pristine nature of Dickensian memorabilia, as buildings in the area largely remain as they were during Dickens’ time. Walking on High Street gives the look and feel of Dickens’ world.